Lactate to albumin ratio as a determinant of intensive care unit admission and mortality in hospitalized patients with community-acquired pneumonia - Pervin Hancı; Esra Temel; Furkan Bilir; Bilkay Serez Kaya (BMC Pulmonary Medicine)
Abstract Objective Previous studies have shown that the lactate/albumin ratio (LAR) can be a prognostic biomarker in intensive care unit (ICU) patients. However, the usefulness of LAR in predicting mortality and guiding intensive care unit admission in hospitalized patients due to community-acquired pneumonia (CAP) remains unclear. This study aims to evaluate the predictive value of the LAR compared to Pneumonia Severity Index (PSI), Confusion, urea, respiratory rate, blood pressure, 65 years or older (CURB-65), and quick-Sequential Organ Failure Assessment (q-SOFA) scores in determining the need for ICU admission and mortality among hospitalized patients with CAP. Methods Adult patients diagnosed and hospitalized with community-acquired pneumonia between July 2021 and July 2023 were included. Patients’ demographics, comorbidities, disease severity scores, laboratory findings at the admission and outcomes were recorded. Patients were grouped and compared according to admission place (ward or ICU). Results PSI, CURB-65, q-SOFA scores, and LAR were higher in ICU patients than in those admitted to the ward. Regarding the ICU admission, the AUC values for PSI, CURB-65, q-SOFA and LAR were 0.794 (95% CI: 0.737–0.843) (p < 0.001), 0.825 (95% CI: 0.771–0.870) (p < 0.001), 0.755 (0.690–0.813) (p < 0.001), and 0.749 (95% CI: 0.689–0.802) (p < 0.001), respectively. Regarding the mortality, the AUC values for PSI, CURB-65, q-SOFA, and LAR were 0.722 (95% CI: 0.661–0.778) (p < 0.001), 0.743 (95% CI: 0.683–0.797) (p < 0.001), 0.645 (0.575–0.711) (p: 0.02), 0.761 (95% CI: 0.702–0.814) (p < 0.001), respectively. There wasn’t any difference detected in pairwise comparisons of ROC curves. Conclusion In this study, LAR was found to be a good predictor of ICU admissions and mortality in hospitalized patients with CAP and was non-inferior to PSI, CURB-65, or q-SOFA scores.